2016
DOI: 10.1177/2158244016662901
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Teachers’ Professional Development Needs, Impacts, and Barriers

Abstract: The article reports on findings from the TALIS (Teaching and Learning International Survey) 2013 study for Abu Dhabi which gathered teachers' views on teaching and learning with a focus on professional development. The aim of this study is to better understand teachers' perceptions of professional development needs and impacts as well as the barriers faced by teachers from secondary schools in Abu Dhabi. The study provides some insights into the variations of those perceptions relative to other independent var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 43 publications
3
40
0
2
Order By: Relevance
“…Thus, in teaching and learning process, student-teachers are challenged to create encouraging environment with the content relating to VSTEP for students to explore. This findings matches work by Badri (2016), who claims that proficiency test might limit the teachers and learners to whatever content, organization, or style is dictated by the organizer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, in teaching and learning process, student-teachers are challenged to create encouraging environment with the content relating to VSTEP for students to explore. This findings matches work by Badri (2016), who claims that proficiency test might limit the teachers and learners to whatever content, organization, or style is dictated by the organizer.…”
Section: Discussionsupporting
confidence: 87%
“…They have more targets for teaching career as well as progressive attitude in training generations of students. Through interviews, the researchers (Badri et al, 2016) found that the teachers test results had no direct personal impact on them, the teacher became more comfortable and fearful, so the effect of the test also dropped.…”
Section: Student-teachers' Attitudes Toward Vstep As Professional Devmentioning
confidence: 99%
“…The continuous feedbacks and evaluations should be able provide effective recommendations and redesign when necessary. Badri et al (2016) used the same sample and reported ANOVA of the individual variables of the two constructs of perceived needs and perceived impacts of professional development. Their study provided some insights into the variations of those perceptions relative to other independent variables such as teachers' age and gender and type of schools.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies related to the use of technology in secondary schools (Fullan, 2001;Senge, 1990;Michael, 1998;Johnston & Cooley, 2001;Hamzah, Juraime, Hamid, Nordin & Attan, 2014) agree that principals play a key role in the use of ICT in the classroom. Additionally, studies such as by McLeod (2011), Wang (2010), Badri, Alnuaimi, Mohaidat, Yang, and Al Rashedi (2016), and Evers, Van der Heijden, and Kreijns (2016) suggest that professional development should be further examined.…”
Section: Introductionmentioning
confidence: 99%